Integrability for Solutions of Anisotropic Obstacle Problems. (28th June 2012) - Gao, Hongya; Zhang, Yanjie; Li, Shuangli
Abstract : This paper deals with anisotropic obstacle problem for the𝒜 -harmonic equation∑ i = 1 n D i ( a i ( x, D u ( x ) ) ) = 0 . An integrability result is given under suitable assumptions, which show higher integrability of the boundary datum, and the obstacle force solutionsu have higher integrability as well.